2020
DOI: 10.4049/jimmunol.2000222
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of P2X7 Receptor on Th1, Th17, and Regulatory T Cells in Patients with Systemic Lupus Erythematosus or Rheumatoid Arthritis and Its Correlations with Active Disease

Abstract: P2X7 receptor (P2X7R) is highly expressed on immune cells, triggering the release of cytokines and regulating autoimmune responses. To investigate P2X7R surface expression on T helper (Th) 1, Th17, and regulatory T (Treg) cells in patients with systemic lupus erythematosus (SLE) or rheumatoid arthritis (RA) and correlations with disease activity, 29 SLE and 29 RA patients and 18 healthy controls (HCs) were enrolled. We showed that SLE and RA patients had significantly higher levels of plasma cytokines (IFN-g, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Some studies indicate that Th17 cells are positively related to DAS28 of RA patients, while Th1 cells have no correlation with disease activity of RA 37‐39 . Besides, there is no study exploring the relationship between MALT1 and disease activity of RA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies indicate that Th17 cells are positively related to DAS28 of RA patients, while Th1 cells have no correlation with disease activity of RA 37‐39 . Besides, there is no study exploring the relationship between MALT1 and disease activity of RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that Th17 cells are positively related to DAS28 of RA patients, while Th1 cells have no correlation with disease activity of RA. 37 , 38 , 39 Besides, there is no study exploring the relationship between MALT1 and disease activity of RA patients. Partially in line with previous studies, we found that MALT1, Th1, and Th17 cells were all positively correlated with disease activity of RA patients; nonetheless, the correlation coefficients of Th1 cells and RA disease activity related indexes were relatively weak.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that significantly elevated proportions of circulating Th17 and Th1 cells stained positive for P2X7 in samples from either SLE or RA patients compared with healthy controls. The percentage of P2X7-expressing Th17 cells correlated with both DAS28 and serum concentrations of IL-1β ( 184 ). Activation of the P2X7 receptor and NLRP3-dependent IL-1β production by dendritic cells is important for priming of T cells, and this pathway was shown to regulate CD8+ T cell activity in the anti-cancer immune response ( 185 ) and Th17 differentiation in arthritis models ( 181 ).…”
Section: Mitochondrial Dampsmentioning
confidence: 99%
“…T cells have been found to play a crucial role in the pathogenesis of SLE [ 12 , 13 ], among which CD4 + T cells are active mediators for the pathogenesis of SLE [ 13 , 14 ]. Cytokine dysregulation promotes immune dysfunction, and tissue inflammation is one of the hallmarks of SLE [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%